Subtilisin QK-2: secretory expression in Lactococcus lactis and surface display onto gram-positive enhancer matrix (GEM) particles. Issue 1 (December 2016) - Mao, Ruifeng; Zhou, Kangping; Han, Zhenwei; Wang, Yefu
Abstract Background Purified from the supernatant ofBacillus subtilis QK02 culture broth, Subtilisin QK-2 is a type of effective thrombolytic reagent that has great exploitable potential. However, the unbearable flavor that occurs with fermentation and the complicated methods that are required to obtain pure products limit the application of this enzyme. Lactic acid bacteria (LAB)-based delivery vehicles are promising as cheap and safe options for medicinal compounds. The secretory expression and surface display using LAB may popularize Subtilisin QK-2 more easily and conveniently with minimal adverse effects. Results Subtilisin QK-2 was expressed successfully in two forms using lactic acid bacteria. For the secretory expression inLactococcus lactis, Subtilisin QK-2 was efficiently secreted into the culture using the promoter PnisA and signal peptide SPUsp . The expression levels were not different inL. lactis NZ9000 and NZ3900 without the effect of different selection markers. However, leaky expression was only detected inL. lactis NZ3900. The biological activity of this secreted Subtilisin QK-2 was enhanced by modulating the pH of medium to slightly alkaline during induction and by codon optimization of either the entire gene sequence (qk′ ) or only the propeptide gene sequence (qkpro′ ). For surface display onto gram-positive enhancer matrix (GEM) particles, n LysM repeats from the C-terminal region of the major autolysin AcmA ofL. lactis were fused to either the C-terminus (n = 1, 3, 5) or the N-terminus (n = 1) of the Subtilisin QK-2. These fusion proteins were secreted into the culture medium, and the QK-3LysM was able to bind to the surface of various LAB GEM particles without a loss of fibrinolytic activity. Furthermore, the binding capacity significantly increased with a higher concentration of QK-3LysM. Compared to the free-form Subtilisin QK-2, the QK-3LysM displayed on the surface of GEM particles was more stable in the simulated gastric juice. Conclusions Combined with the safety and popularity of LAB, Subtilisin QK-2 may be easily applied worldwide to prevent and control thrombosis diseases.